2020
DOI: 10.1186/s40364-020-00217-0
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of potential biomarkers associated with severity of coronavirus disease 2019 (COVID-19)

Abstract: Background: Prognostic factors for the Coronavirus disease 2019 (COVID1-9) are not well established. This study aimed to summarize the available data on the association between the severity of COVID-19 and common hematological, inflammatory and biochemical parameters. Methods: EMBASE, MEDLINE, Web of sciences were searched to identify all published studies providing relevant data. Random-effects meta-analysis was used to pool effect sizes. Results: The bibliographic search yielded 287 citations, 31 of which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
138
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(154 citation statements)
references
References 99 publications
7
138
2
7
Order By: Relevance
“…ISARIC‐4C includes blood urea nitrogen and CRP, whereas COVID‐GRAM include lactate dehydrogenase (LDH) and direct bilirubin. CRP and LDH were already described to be associated to advanced pulmonary disease in COVID‐19, 25,26 as well as kidney damage and increased blood urea nitrogen, 27 as confirmed in our study. Conversely, we cannot confirm the usefulness of bilirubin evaluation since the hepatic involvement in our cohort was limited.…”
Section: Discussionsupporting
confidence: 89%
“…ISARIC‐4C includes blood urea nitrogen and CRP, whereas COVID‐GRAM include lactate dehydrogenase (LDH) and direct bilirubin. CRP and LDH were already described to be associated to advanced pulmonary disease in COVID‐19, 25,26 as well as kidney damage and increased blood urea nitrogen, 27 as confirmed in our study. Conversely, we cannot confirm the usefulness of bilirubin evaluation since the hepatic involvement in our cohort was limited.…”
Section: Discussionsupporting
confidence: 89%
“…In an article by Yafei Zhang, results showed that there was no significant difference between the CRP levels after transferring the patients to ICU [ 36 ]. Although an increase in CRP level was seen in people with COVID-19 according to some study reports, based on statistical analysis, it was declared that this index may not be a good indicator of the expression of COVID-19 [ 45 ] However, a meta-analysis reported CRP level increased in severe form of COVID-19 [ 63 ]. Furthermore, In our study, based on our analysis, we found that non-survival individuals had higher CRP levels than survival people.…”
Section: Discussionmentioning
confidence: 99%
“…As described by Balogun et al [ 7 ], these factors could explain a prolonged hospital stay for DVT patients and give reasons to investigate sepsis, cancer and bedrest as competing risk factors when no complications were noticed in non-DVT patients. Thirdly, inflammatory syndrome, acting as a classical indicator of COVID-19 severity [ 8 ], can slightly worsen a prothrombotic state. Therefore, we hypothesized that in addition to known competing factors such as advanced age, unfavourable NIHSS scores, and medical complications leading to a long hospital stay, a stronger inflammatory syndrome in non-severe COVID-19 can slightly worsen a prothrombotic state that favours DVT.…”
Section: Discussionmentioning
confidence: 99%